2023
DOI: 10.1007/s00296-023-05283-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the incidence, management and prognosis of new-onset autoimmune connective tissue diseases after COVID-19

Abstract: A literature review on new-onset autoimmune connective tissue diseases (ACTDs) following COVID-19 is lacking. We evaluated potential associations between COVID-19 and the development of new-onset ACTDs. The “population” was adults with disease terms for ACTDs, including systemic lupus erythematosus (SLE), Sjogren’s syndrome, systemic sclerosis (SSc), idiopathic inflammatory myositis (IIM), anti-synthetase syndrome, mixed CTD and undifferentiated CTD, and “intervention” as COVID-19 and related terms. Databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
2
7
0
1
Order By: Relevance
“…In our sample, the majority of respondents were female, with a mean age of over 50 years and an average duration of symptom onset of more than 3 weeks. This is consistent with a systematic review that reported a higher incidence of new‐onset SAIDs in female patients of a similar age and duration of onset (64.3% female, and 51.1 years and 23.7 days, respectively) 11 . Another systematic review reported similar findings (62.5% female, and 56 years and 11 days, respectively) 12 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our sample, the majority of respondents were female, with a mean age of over 50 years and an average duration of symptom onset of more than 3 weeks. This is consistent with a systematic review that reported a higher incidence of new‐onset SAIDs in female patients of a similar age and duration of onset (64.3% female, and 51.1 years and 23.7 days, respectively) 11 . Another systematic review reported similar findings (62.5% female, and 56 years and 11 days, respectively) 12 …”
Section: Discussionsupporting
confidence: 89%
“…Our study reported IIM to be the most commonly self‐reported new‐onset SAID following COVID‐19 vaccination, which is otherwise a rare disease. This is similar to the disease distribution found in a systematic review, with IIM being the most common connective tissue disease (CTD) disorder after COVID‐19 vaccination 11 . The fact that IIM is the most reported SAID likely reflects our sampling strategy/bias.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) drives a marked inflammation with risk of cytokine storm ( 36 ): A very recent study has linked SARS-CoV-2 infection to the onset of different systemic autoimmune diseases, and the most common disorder found in adults was idiopathic inflammatory myopathy, with 4 cases of dermatomyositis, after an average time of 23.7 days from COVID-19 diagnosis ( 37 ). Holzer et al.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Autoantibodies known to occur in several autoimmune diseases have been detected in patients with COVID-19 during or after the illness [2]. In addition, several new autoimmune and autoinflammatory conditions have been reported, such as idiopathic inflammatory myositis or systemic lupus erythematous, after COVID-19 infections [3]. A study by Park et al [4] in this issue of the Korean Journal of Internal Medicine draws attention to the relationship between COVID-19 infection and autoimmunity.…”
Section: Significance Of Antinuclear Antibodies In Patients With Covi...mentioning
confidence: 99%